PENGARUH ORGANIZATIONAL CULTURE TERHADAP FINANCIAL PERFORMANCE MELALUI INTELLECTUAL CAPITAL SEBAGAI VARIABEL INTERVENING - Glenn Averill; Devie Devie Devie (Business Accounting Review, 2018)
This research was conducted to find out the influence of Organizational Culture towards Financial Performance with Intellectual Capital as Intervening Variable in the manufacturing company located in Surabaya and surrounding areas. Organizational Culture became an important variabel that affected firms’ financial performance. Another variable such as Intellectual Capital also contributed in increasing the firms’ financial performance. On the other hand, Intellectual Capital could not be separated from the support of Organizational Culture.The data analysis techniques used in this research was partial least square to describe the influence of the variables. The research results showed that the Organizational Culture and Intellectual Capital affected the financial performance in a positive and significant on manufacturing company around Surabaya.